Improvement of Brinjal-T. Aman -Cabbage Cropping Pattern in Tangail Region - Khan, MAH; Naher, Q; Rahman, MM; Tasmima, T; Sultana, N (Bangladesh Journal of Agricultural Research, 2023)
The experiment was conducted at the farmers’ field of FSRD site Deldwar, Tangail to evaluate the agro-economic performance of Okra-T.Aman-Cabbage cropping pattern against farmers’ existing pattern Brinjal-T.Aman rice-Cabbage through incorporation of high yielding varieties and improved management practices during 2018 to 2020. Two cropping pattern viz., Okra-T.Aman rice-Cabbage improved pattern and Brinjal-T.Aman rice-Cabbage farmers’ existing pattern were the treatments variables. The experiment was laid out in randomized complete block design with five dispersed replications Mean data showed that the improved management practices for Okra-T.Aman rice-Cabbage cropping pattern provided higher rice equivalent yield (41.42 t ha-1), production efficiency (368 kg ha-1 day-1) and land utilization index (78 %) over farmers existing pattern Brinjal-T.Aman rice-Cabbage. Average gross return Tk. 667945 ha-1 and gross margin Tk. 452105 ha-1 of improved pattern were 24 and 33 % higher, respectively compared to that of farmers’ pattern with only 8 % extra cost. The marginal benefit cost ratio, land utilization index and production efficiency indicated the superiority of the improved pattern over the farmers’ practices. Bangladesh J. Agril. Res. 47(3): 323-232, September 2022